A Rare Case of Brugada Phenocopy in A Patient With Takotsubo Cardiomyopathy Masquerading as an Acute Coronary Syndrome. Issue 3 (December 2020) - Mahadevappa, Manjappa; Kulkarni, Prashanth; KS, Poornima
Brugada phenocopies (BrP) are clinical entities that are etiologically distinct from true congenital Brugada syndrome. BrP are characterized by type 1 or 2 Brugada electrocardiogram (ECG) patterns in precordial leads V1-V3. However, BrP is elicited by various underlying clinical conditions such as myocardial ischemia, pulmonary embolism, electrolyte abnormalities, or poor ECG filters. Upon resolution of the inciting underlying pathological condition, the BrP ECG subsequently normalizes. Takotsubo (octopus fishing pot) cardiomyopathy (TCM) also known as stress cardiomyopathy is an acute cardiac condition characterized by transient systolic dysfunction of the left ventricular apex and mid-ventricle with depressed LV function mimicking acute coronary syndrome (ACS) and recovers within a few weeks. TCM is most commonly seen in postmenopausal women with intense physical and or emotional stress. We are reporting a rare case of BrP in a patient with TCM masquerading as ACS posing a diagnostic and therapeutic challenge.